Giant Primary Scrotal Lipoma: A Rare Entity with Diagnostic Pitfalls - Louis Vignot; Elie Saad; Michael Peyromaure; Nicolas Barry Delongchamps (Case Reports in Urology)
Primary scrotal lipomas are rare. We describe the case of a 47-year-old male with a giant scrotal lipoma who underwent a surgical excision. We report the clinical and radiological approach as well as the treatment of this atypical benign tumor.